DETECTING LEAD TOXICITY OF CABBAGE AND LETTUCE CROPS BY USING INFRARED IMAGES - Tarek FOUDA; Eltaher MADY; Nouri AL BAY; Ashraf SWIDAN; Shimaa SALAH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of this study was the possibility of using IR images to detect lead toxicity for Cabbage and lettuce crops. Lead Pb-contaminated were watered with 3 levels of (2, 4,and 6 mg/lit). To distinguish the heavy metal contamination and their impact on vegetative characteristics. For plants, the results showed a poisoning level (2mg/liter). The maximum MTD and NRCT values were 6.3 and 4, respectively. The lowest values under the same level of poisoning were 0.89 and 0.01. The greatest MTD and NRCT values at the poisoning level (4 mg/liter) were 5.3 and 2.5, respectively. The lowest values at the same level of poisoning were 0.19 and 0.07. Additionally, at the same time period with the same poisoning level (6 mg/liter), the maximum values for MTD and NRCT were 5.8 and 0.24, and the lowest values were 1.5 and 0.1. C. For lettuce plants, at a toxic dose of 2 mg/liter. The MTD and NRCT values ranged from 6.2 and 1.5 to 0.2 and 0.09 at the same amount of poisoning, respectively. Intoxication (4 mg/liter). In poisoning level (4mg/liter) the highest values for MTD and NRCT were 3.2 and 1.87 also the minimum value in the same level of poisoning were 0.2 and 0.08. And in the same period with poisoning level (6mg/liter) the highest values for MTD and NRCT were 2.88 and 1.55 also the minimum value in the same level of poisoning were 0.22 and 0.05. Linear regression analysis was performed to predict MTD and NRCT at different days were done .The maximum value of cabbage temperature of air, soil, canopy, and leaf was 35, 30, 27, and 23 °C, also showed the minimum value for the same indices were 17.4, 16.2, 15.5 and 14.5 °C, in poisoning level (2mg/liter). In poisoning level (4mg/liter) the maximum value of cabbage temperature of air, soil, canopy, and leaf were 40, 35, 28, and 31 C, also showed the minimum value for the same indices were 14, 15, 16. and 17.9 °C. While the maximum value of lettuce temperature of air, soil, canopy, and leaf was 33.6, 30.6, 28.6, and 26 °C, also showed the minimum value for the same indices were 18.9, 17.8, 15.4 and 13.6 °C, in poisoning level (2mg/liter). In poisoning level (4mg/liter) the maximum value of Lettuce temperature of air, soil, canopy, and leaf were 40, 32.7, 28.6, and 26 °C, also showed the minimum value for the same indices were 24, 21, 18. and 13.7 °C.